OCULO-AURICULO-VERTEBRAL SPECTRUM ASSOCIATED WITH ABERRANT SUBCLAVIAN ARTERY IN AN INFANT WITH RECURRENT RESPIRATORY DISTRESS - Amanda Rosa Pereira; Carlos Henrique Paiva Grangeiro; Larissa Cerqueira Pereira; Letícia Lemos Leão; Juliana Cristina Castanheira Guarato (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To describe an infant with craniofacial microsomia and recurrent respiratory distress associated with aberrant right subclavian artery in order to review its most frequent congenital anomalies and alert the pediatrician to its rarer and more severe complications. Case description: This case report involves an 18-month-old male infant, only son of non-consanguineous parents. At birth, the child presented craniofacial dysmorphisms (facial asymmetry, maxillary and mandibular hypoplasia, macrostomia, grade 3 microtia, and accessory preauricular tag) restricted to the right side of the face. Additional tests showed asymmetric hypoplasia of facial structures and thoracic hemivertebrae. No cytogenetic or cytogenomic abnormalities were identified. The patient progressed to several episodes of respiratory distress, stridor, and nausea, even after undergoing gastrostomy and tracheostomy in the neonatal period. Investigation guided by respiratory symptoms identified compression of the esophagus and trachea by an aberrant right subclavian artery. After surgical correction of this anomaly, the infant has not presented respiratory symptoms and remains under multidisciplinary follow-up, seeking rehabilitation. Comments: Craniofacial microsomia presents a wide phenotypic variability compared to both craniofacial and extracraniofacial malformations. The latter, similarly to the aberrant right subclavian artery, is rarer and associated with morbidity and mortality. The main contribution of this case report was the identification of a rare anomaly, integrating a set of malformations of a relatively common condition, responsible for a very frequent complaint in pediatric care.